Job satisfaction and affective commitment: a study of employees in the tourism industry in Sarawak, Malaysia - Lew, Tek (Inderscience Enterprises Ltd, 2008)
This study examines what motivates the employees involved in the tourism industry in Sarawak, Malaysia, their level of job satisfaction and the influence of job satisfaction on affective commitment. Meanwhile, this study also examines whether age moderates the relationship. The tourism industry is chosen as the industry for analysis of job satisfaction and affective commitment as it is the critical industry accommodating the increasing number of visitors to Sarawak. Hierarchical regression analysis was used to analyse the data of the study. Satisfaction towards salary was found to have a significant positive relationship with affective commitment while satisfaction towards supervision showed significant positive relationships with normative commitment.